Influence of Drying Temperature on Phenolic Acids Composition and Antioxidant Activity of Sprouts and Leaves of White and Red Quinoa - Urszula Złotek; Urszula Gawlik-Dziki; Dariusz Dziki; Michał Świeca; Renata Nowak; Enrique Martinez (Journal of Chemistry)
The aim of this study was to evaluate the influence of drying temperature on the phenolic acids profile and antioxidant activity of sprouts and leaves red and white Chenopodium quinoa (RQ and WQ, respectively). Four-day sprouts and leaves dried at 30, 45, and 60°C were tested. All sprouts contained significant amounts of phenolic compounds; however, higher content was determined in the RQ sprouts. Phenolic compounds from WQ sprouts seem to be thermostable in the studied temperature range, whereas total phenolics content in RQ sprouts decreased significantly after drying in the 60°C. Content of vanillic and p-coumaric acids did not differ significantly between sprouts dried at the same conditions; however, their level decreased in the high temperature. Irrespective of the drying temperature, higher activity against ABTS free radicals and reducing power was observed in the case of RQ sprouts extracts. Sprouts dried at 30°C had a higher ability to scavenge hydroxyl radicals. RQ sprouts were characterized by about two times higher antioxidant activity regardless of the method used. No significant differences between total phenolics (TPC) and flavonoids content in RQ and LQ leaves were found. In the both cases, decrease of TPC was observed after drying in the highest temperature. The leaves do not differ too much in terms of the phenolic acids profile, whereas the differentiating factor is thermal processing. Leaves of both quinoa contained thermostable compounds able to scavenge hydroxyl radicals. Reducing power and ability to scavenge OH radicals were correlated with all components of quinoa sprouts which suggest synergism between them and does not indicate the key role of a particular compound in creating antioxidant capacity. Germination and subsequent oven-drying at 30°C of quinoa seeds significantly increased the antioxidant properties compared with raw seeds. Also, in the case of leaves, the best results were obtained after drying at 30°C.